The benefits of prisoner participation in interdisciplinary learning. Issue 8 (16th November 2016) - Raikes, Ben; Balen, Rachel
Abstract: This paper considers the provision of an inter-disciplinary workshop day held for Social Work, Police and Nursing students at a UK university. The focus of the day was to give the students an insight into the reality of being a mother in prison, and the impact that having a mother in prison has upon children. A key feature of the day was the involvement of a group of imprisoned mothers from an open prison, who shared their experiences and engaged with students in small groups. The workshop allowed the stereotypes that the prisoners and student professionals held in relation to one another to be challenged. The planning, aims, process and outcomes of the day are considered along with feedback from those taking part. Students reported increased awareness of the stigma faced by this often overlooked vulnerable group of service users, an increased recognition of the needs of children with mothers in prison and an appreciation of the power of interdisciplinary working to deliver a good service. The imprisoned mothers welcomed the chance to educate the students about the issues faced by themselves and their children, and they found the experience of participating to be positive and empowering.